Equity return expectations and financial wealth holdings of U.S. households - Marty Cotwright; Swarn Chatterjee (Open Economics, 2022)
This paper examines the association between stock market return expectations and financial wealth holdings of older adults using the 2016 wave of the Health and Retirement Study. Our study finds that less than 30% of individuals assigned a greater than 50% probability that the market will earn a positive nominal return in the following year. However, considerable heterogeneities were observed across racial/ethnic groups. Health status, the cognitive functioning of older adults, and expectations of positive stock market return were positively associated with greater financial wealth holdings among households. Our study also finds that older age, and being female were associated with a higher probability of expected equity returns in the following period. Health status, cognition, and equity return expectations were positively associated with the financial wealth holdings of households. African Americans, Hispanics, and other races were negatively associated with the probability of equity return expectations and financial wealth holdings when compared with the reference group of non-Hispanic Whites. Overall, this study contributes to the literature by applying a unique mathematically derived measure of future return expectations, and extends the literature on equity return expectations and the financial portfolios of households. The negative association between being African American or Hispanic and financial wealth holdings is concerning. The findings from this study inform policy makers, and underscore the need for prioritizing programs and policies that can be play a critical role in building human capital, in promoting financial capability, and in bridging the financial wealth gap for households belonging to the disadvantaged and underserved racial ethnic groups.
Keywords: 330; Cognitive Ability; Financial Wealth; Market Expectations; Positive Nominal Return